Universitas Psychologica: 10 Years of Constant Change in Editorial and Content Management - López López, Wilson; Pontificia Universidad Javeriana (2011)
Our journal is turning 10 years old in 2011. During this period, we have experienced deep and significant transformations, that have led us to change our printed format and to modify the Web proposal, which has merged an aesthetical development with the Open Journal System (OJS) for content management. This web has generated two published articles, where we show how our proposal is a model for journal websites all around the world (the articles can be found in http://journals.sfu.ca/src/index.php/src/article/viewFile/20/35 and http://www.apa.org/international/pi/2009/12/panamerican- journal.aspx). The publication of these articles suggest that we are going the right way. Another indicator is the coverage of the journal in the ISI WoS and Scopus systems, which now deliver information about the way our contents are used, expressed in citations. The success and international visibility achieved by Universitas Psychologica has also brought some difficulties – what I call a “success crisis”. This crisis has been seen in the exponential increase in article submissions – over 1200 in the past two years, and in the need to grow from two issues per year, 30 articles, to three issues with 60 articles per year. The situation has demanded that we look for peer reviewers all over the Iberoamerican world, and has brought about an increase in articles written in English and Portuguese, which has made content management more complex. On the other hand, conceptual, methodological, and thematic plurality, has given us something else to worry about, since we do not still have a critical mass of peer reviewers. Moreover, the reviewers in Iberoamerica have different skills, which has led to divergent opinions, and this has, in turn, had an influence on reviewing times – we have not been able to provide timely reviews in some cases. Of course, and more than once, authors have expressed their inconformity with the situation, despite enough justification of the realities of Iberoamerican academic dynamics, which they sometimes fail to acknowledge. The challenge for us is to optimize peer reviewer search and invitation times, and to increase the quality of the assessments and the answers to the authors. We will continue to beg for your patience: this problem will not be solved in the short term, if we want to take every article to peer reviewing, with the associated learnings for our community. As we have previously mentioned, Universitas Psychologica also has the challenge of consolidating itself as a referential journal in our community, which cannot be achieved by means different than the collaboration obtained from all the authors, in terms of an increase in citations to the Journal. The Scimago SJR indicators stemming from Scopus and the preliminary data from ISI WoS, that we expect to receive in the new JCR to be published this year, show an important increase in citations: we went from four citations in 2008, to 30 in 2009. The Local SJR seems to suggest that our community is giving us more recognition as a quality journal. Moreover, we see that authors understand that publishing in English increases the likelihood of getting their papers read worldwide, and today, Universitas Psychologica is being consulted all over the world. Nevertheless, it is evident that it is not enough to publish in English, but that it is also important to tell our peers about our articles. And the challenge for those who publish in Spanish and Portuguese is that communities publishing in these two languages use the contents written in both languages. I understand that this is also a process of cultural change that will take time, but we are also carrying out the actions necessary to strengthen this path in the region, and simultaneously to consolidate ourselves as an international journal. I must also mention that, during the past ten years, the journal has committed itself to cooperating with open access systems developed in the region, such as SciELO (http://www.scielo.org.co), Redalyc (http://redalyc.uaemex.mx), Pepsic (http://pepsic.bvsalud.org) and the Virtual Health Library - Psychology (http://www.bvs-psi.org.co). In these years as an editor for Universitas Psychologica, I have been appointed as a member of the SciELO Colombia committee (2008-2009), I have accompanied the development of the Virtual Health Library – Psychology (BVS Psicología), and I have been appointed as the first director of the Redalyc Psychology Portal (Psicoredalyc), an initiative sponsored by the FIAP (Iberoamerican Association of Psychology Federations), covering over 60 journals from the whole continent. At the end of 2010, I was appointed President-Coordinator of Redalyc’s International Advisory Committee. It is also noteworthy that, in this line of consolidating visibility networks in Latin America, we have been carrying out the Iberoamerican Psychology Journal Editors Meetings, and we have created the Iberoamerican Psychology Journals Network. I am sure that these actions will contribute to the strengthening of our academic community. We understand that we still have much to learn, and that there are several actions that we need to perform in order to continue to benefit from your confidence and to continuously improve our journal. Last, I want to stress the collaboration of the editorial coordinators and teams; of the scientific, editorial, and peer-reviewer committees, of the volunteer students, and the people from the Javeriana Publishing house. Specially, the unconditional, exhaustive, and rigorous work of the coordinators (Camilo Hurtado and then Luis Manuel Silva), without whose work, the journal would not have the quality that is being recognized by the international community. Happy 10 years for Universitas Psychologica, and thank you all for these road of confidence that we have been walking. Wilson López-López Editor